Educational Tafsir of Social Piety in the Qur'an: Strengthening Islamic Character Education in Multicultural Society - Fathurrohman, Asep Ahmad (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
Social piety is an important dimension in Islamic education because it connects individual religiosity with social responsibility in a multicultural society. This research aims to analyze the concept of social piety in the Qur'an through the perspective of educational interpretation and formulate its implications for strengthening Islamic character education. This research uses a qualitative approach with the type of literature research. Data is obtained from verses of the Qur'an related to social piety, such as QS. al-Baqarah [2]: 177, QS. al-Mā'ūn [107]: 1–7, QS. al-Ma'idah [5]: 2, QS. al-Naḥl [16]: 90, and QS. al-Ḥ ujurāt [49]: 10–13, as well as classical and contemporary tafsir books. The analysis was carried out in a descriptive-analytical manner with a thematic interpretation approach. The results of the study show that social piety in the Qur'an includes the integration of faith, worship, social concern, help, justice, ihsan, brotherhood, and respect for diversity. These values are the basis for Islamic character education that not only forms ritually obedient individuals, but also caring, fair, inclusive, and socially responsible. This study concludes that the educational interpretation of social piety can be the basis for strengthening Islamic character education in a multicultural society.